Rainbow milk : a novel - Mendez, Paul, 1982- (Doubleday, 2021)
"An essential and revelatory coming-of-age narrative following nineteen-year-old Jesse McCarthy as he grapples with his racial and sexual identities against the backdrop of his Jehovah's Witness upbringing"--